The technology of formation of would-be managers’ constructive interaction skills - Гагіна, Н. В. (Educational Dimension, 2012)
Hahina N. The technology of formation of would-be managers’ constructive interaction skills. The technology of formation of would-be managers’ skills of constructive interaction in a conflict situation is introduced in the article. The technology components are determined. The formation of constructive interactionskills is carried out in accordance with the followings stages: diagnostic-motivational, theoretical, training, reflection-correctional and creative.